2009
DOI: 10.1021/jp903126f
|View full text |Cite
|
Sign up to set email alerts
|

Adenine− and Adenosine Monophosphate (AMP)−Gold Binding Interactions Studied by Surface-Enhanced Raman and Infrared Spectroscopies

Abstract: Understanding the interactions of biomolecules with noble metal surfaces is critical to our development of functional biomedical nanodevices and accurate biosensors. Here we use surface enhanced Raman spectroscopy (SERS) and surface enhanced infrared absorption spectroscopy (SEIRA) on Au nanoshell substrates to study the interactions of adenine and two adenine derivatives, thiolated polyadenine single-stranded DNA (polyA) and adenosine monophosphate (AMP), with Au surfaces. pH-dependent conformational changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
111
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 64 publications
19
111
0
2
Order By: Relevance
“…All complexes are formed by linkage of Ag atoms to nitrogen atoms in a side-on orientation, which implies that adenine prefers to adopt an end-on adsorption mode on silver nanoparticles. As reported by many experimental and computational studies, [9,12,18,19] Figure 2 shows that adenine is bound to the cluster through N1, N3, or N7 in an upright orientation for the S complexes (a, b, c, and e), in a slightly tilted orientation for the V complexes (a1, b1, c1, and e1), and in an orientation perpendicular to one edge for the E complexes (a2, b2, c2, and e2). Furthermore, adenine could be adsorbed on the silver cluster through the external amino group in complex f1, which is a model of flat-on adsorption on silver surfaces.…”
Section: Normal Raman Spectra (Nrs) Of Adenine-ag 20 Complexessupporting
confidence: 56%
See 2 more Smart Citations
“…All complexes are formed by linkage of Ag atoms to nitrogen atoms in a side-on orientation, which implies that adenine prefers to adopt an end-on adsorption mode on silver nanoparticles. As reported by many experimental and computational studies, [9,12,18,19] Figure 2 shows that adenine is bound to the cluster through N1, N3, or N7 in an upright orientation for the S complexes (a, b, c, and e), in a slightly tilted orientation for the V complexes (a1, b1, c1, and e1), and in an orientation perpendicular to one edge for the E complexes (a2, b2, c2, and e2). Furthermore, adenine could be adsorbed on the silver cluster through the external amino group in complex f1, which is a model of flat-on adsorption on silver surfaces.…”
Section: Normal Raman Spectra (Nrs) Of Adenine-ag 20 Complexessupporting
confidence: 56%
“…[8][9][10][11][12][13][14][15][16][17][18] Of the four nucleobases, adenine ( Figure 1) is an extremely important molecule with which to study chemisorption to Ag or Au nanoparticle surfaces in detail. Adsorption of adenine on noble metal surfaces has been studied by SERS experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 However, they are absent in the characteristic peaks from phosphate and sugar moieties on ssODN as a result of the small Raman cross-section of them. 36 Moreover, we also evaluated the signal performance of the SERS chip fabricated with different sizes of poly(21dA)−AuNPs (∼60, ∼75, ∼90, and ∼100 nm). It is found that the SERS chip fabricated with poly(21dA)−AuNPs of ∼100 nm possesses the most sensitive SERS signal ( Figure S5 of the Supporting Information), which is optimal for "turn-off" SERS detection.…”
Section: Morphological Characterization Of the Sers Chipmentioning
confidence: 99%
“…Both 6-azaC and 5-azaC nucleosides have a wide spectrum of biological properties that result in pharmacological activity, primarily antitumor and antiviral effects [1][2][3][4][5][6][7] . There have been extensive experimental [8][9][10][11][12][13][14][15][16][17] and theoretical [18][19][20] studies of biomolecules on gold and other Group 11 metal surfaces, to a large extent focused on amino acids, nucleobases, and their polymers -oligonucleotides, peptides, proteins, etc. We have chosen the present set of compounds based on (and including) the nucleobase cytosine as they are a representative set containing a standard nucleobase, as well as novel functional groups in the derivatives, such as one would expect to find in new pharmaceuticals, for example.…”
Section: Introductionmentioning
confidence: 99%